Optimization and Testing of Young Coconut Peeling Machines for Productivity Enhancement - Muttaqin, Ahmad Nurul; Mihdar, Uswatul Hasanah; Arfandy, Arfandy; Ariputra, A.; Wicaksono, Ariawan Bayu (Universitas Muhammadiyah Yogyakarta, 2025)
This research aims to develop and optimize a machine for peeling young coconut skin, increasing production efficiency and improving the quality of peeling results. The research background is based on the need for more efficient tools compared to manual methods, which are only capable of peeling around 45 coconuts per hour. Research methods include designing, assembling, and testing machines with various knife models and electric motors. The design process uses Autodesk Inventor software, and testing is carried out by measuring the stripping time and the quality of the stripping results. This study analyzes the impact of different knife models and motor power variations on the efficiency of young coconut peeling, using a machine with a 1/2 HP electric motor at 1400 RPM capable of peeling 68 coconuts per hour, achieving a 51% increase in production compared to manual methods not only increases time and energy efficiency but also produces more consistent products. The conclusion shows that this young coconut skin peeling machine is able to increase productivity and the quality of peeling results, providing an innovative solution in the young coconut processing industry. This research suggests the use of peeling machines to increase efficiency and quality in processing young coconuts, optimize production, and reduce the risk of work injuries that often occur with manual methods.